Early antenatal care visit: a systematic analysis of regional and global levels and trends of coverage from 1990 to 2013 - Moller, Ann-Beth; Petzold, Max; Chou, Doris; Say, Lale (The Lancet global health, 2017)
The timing of the first antenatal care visit is paramount for ensuring optimal health outcomes for women and children, and it is recommended that all pregnant women initiate antenatal care in the first trimester of pregnancy (early antenatal care visit). Systematic global analysis of early antenatal care visits has not been done previously. This study reports on regional and global estimates of the coverage of early antenatal care visits from 1990 to 2013. Data were obtained from nationally representative surveys and national health information systems. Estimates of coverage of early antenatal care visits were generated with linear regression analysis and based on 516 logit-transformed observations from 132 countries. The model accounted for differences by data sources in reporting the cutoff for the early antenatal care visit. The estimated worldwide coverage of early antenatal care visits increased from 40·9% (95% uncertainty interval [UI] 34·6–46·7) in 1990 to 58·6% (52·1–64·3) in 2013, corresponding to a 43·3% increase. Overall coverage in the developing regions was 48·1% (95% UI 43·4–52·4) in 2013 compared with 84·8% (81·6–87·7) in the developed regions. In 2013, the estimated coverage of early antenatal care visits was 24·0% (95% UI 21·7–26·5) in low-income countries compared with 81·9% (76·5–87·1) in high-income countries. Progress in the coverage of early antenatal care visits has been achieved but coverage is still far from universal. Substantial inequity exists in coverage both within regions and between income groups. The absence of data in many countries is of concern and efforts should be made to collect and report coverage of early antenatal care visits to enable better monitoring and evaluation. Department of Reproductive Health and Research, WHO and UNDP/UNFPA/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction.